Examining the Perceptions and Experiences of Dental Care Among Immigrant Free Clinic Patients - Sia Chauhan HBS; Dustin J. Breakfield BS; Danaya Amornnimit; Mason Luceford BS; Brenda Spearman MBA; Akiko Kamimura PhD, MSW, MA (Journal of Patient Experience)
Dental anxiety, the fear related to dental services, can be presented in diverse ways, hindering those in need of dental treatment. This anxiety often results in higher levels of untreated dental issues, affecting oral health-related quality of life primarily due to insufficient dental care or dental care avoidance. Identifying its causes is crucial for effective support and preventative care. This study explores dental care perceptions and experiences among patients at free clinics, offering valuable insights to improve dental support and care for uninsured and underserved individuals. Two hundred ninety-three immigrant patients, mainly Spanish speakers, participated from October 2023 to January 2024. Findings reveal that 14% experienced dental phobia, primarily linked to local anesthetic shots. The majority of patients reported unmet dental needs, highlighting dental care disparities. Understanding how dental phobia contributes to dental care needs is vital to understand, in order to improve oral health outcomes. Future research should address additional barriers like language, finances, and awareness of services. Additionally, exploring other anxiety factors beyond pain, noise, discomfort, and aesthetics is essential.